What Drives Intergenerational Mobility? The Role of Family, Neighborhood, Education, and Social Class: A Review of Bukodi and Goldthorpe’sSocial Mobility and Education in Britain - Salvanes, Kjell G. (Journal of Economic Literature, 2023)
The main finding of Bukodi and Goldthorpe (2019), using social status based on occupation groupings, is that there have not been improvements nor any decline in relative intergenerational mobility in Britain since World War II in terms of social class. Notably, there has not been improvement in the mobility of children from working-class backgrounds relative to other background classes. Importantly, the authors argue strongly that education is not the key determinant of adult success in the labor market. Moreover, improving the educational attainment of children from poor socioeconomic backgrounds does not help improve their labor market performance. This suggests that policies to improve the mobility of children from poor social backgrounds should not include attempts to foster human capital or education policies in general. (JEL D63, I26, I38, J24, J62, N34)